Chlamydia trachomatis among HIV infected patients using PCR technique - Shah, Y; Shrestha, A; Adhikari, N; Pant, KP; Khadka, KS; Acharya, B; Pandey, BD (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Chlamydia trachomatis is a sexually transmitted organism and an important public health problem in the sexually active age group. Limited studies are found regarding the prevalence of Chlamydia trachomatis in Nepal. Moreover, no study in Nepal reports the association of Chlamydia and HIV infection. The current study attempts to determine the burden of Chlamydia on HIV positive patients. Material and Methods: A total of 117 HIV positive patients visiting a HIV clinic in Kathmandu, were screened for Chlamydia infection. For this, Urine samples were collected and analyzed using the Multiplex polymerase chain reaction technique (MPCR) and Agarose gel electrophoresis. DNA isolation was performed using QIAamp DNA and Blood mini kit handbook protocol. Results: C. trachomatis was detected in 4.27% of the total 117 HIV patients. Out of positive cases 60% were males and 40% were females. However, Chlamydia is found more prevalent among females (6.89%) than in males (3.4%). Eighty percent of positive cases were asymptomatic. Conclusion: Chlamydia infection was found less commonly among studied patients and most of those cases were asymptomatic. So there is difficulty in timely detection of C. trachomatis and track the clinical sequel, which might be devastating. Hence, routine checkup is recommended for all suspected cases for timely management of the disease Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (2): 3-10 DOI: http://dx.doi.org/10.3126/jmcjms.v1i2.9261